KSHV Genome Replication and Maintenance - Purushothaman, Pravinkumar; Dabral, Prerna; Gupta, Namrata; Sarkar, Roni; Verma, Subhash C. (Frontiers in Microbiology, 2016)
Kaposi’s sarcoma associated herpesvirus (KSHV) or human herpesvirus 8 (HHV8) is a major etiological agent for multiple severe malignancies in immunocompromised patients. KSHV establishes lifetime persistence in the infected individuals and displays two distinct life cycles, generally a prolonged passive latent, and a short productive or lytic cycle. During latent phase, the viral episome is tethered to the host chromosome and replicates once during every cell division. Latency-associated nuclear antigen (LANA) is a predominant multifunctional nuclear protein expressed during latency, which plays a central role in episome tethering, replication and perpetual segregation of the episomes during cell division. LANA binds cooperatively to LANA binding sites (LBS) within the terminal repeat (TR) region of the viral episome as well as to the cellular nucleosomal proteins to tether viral episome to the host chromosome. LANA has been shown to modulate multiple cellular signaling pathways and recruits various cellular proteins such as chromatin modifying enzymes, replication factors, transcription factors and cellular mitotic framework to maintain a successful latent infection. Although many other regions within the KSHV genome can initiate replication, KSHV TR is important for latent DNA replication and possible segregation of the replicated episomes. Binding of LANA to LBS favors the recruitment of various replication factors to initiate LANA dependent DNA replication. In this review, we discuss the molecular mechanisms relevant to KSHV genome replication, segregation, and maintenance of latency.